Entrepreneurship and innovation in informal productive enterprises: Development of process innovation in a floral arrangement company - Martarello, Rafael de Almeida; Ferro, Débora (REGEPE Entrepreneurship and Small Business Journal, 2021)
Purpose: reporting a process innovation in an informal productive enterprise, inserted in the field of parties, ceremonies and events décor, involving floral arrangements. Methodology: qualitative-descriptive study, with information being obtained through documentary research and case study. Originality/Relevance: this study analyzes an informal productive business, whose practice improvement was conducted based on technological resources. It is relevant because there are only few studies dedicated to technological development, and that thematize the most frequent type of productive enterprise in Brazil. Findings: the process innovation that was conducted has enabled a greater productive efficiency, as well as health, safety and hygiene in the workplace, since it has reduced costs and manufacturing time; and it has eliminated unnecessary procedures that result from the manual method. Theoretical/Methodological Implications: the innovation, developed and described heading from the theories and methodological approach used, in addition to promoting improvement in the ability of adapting to different customer demands, has added an element to the process innovation effects foreseen by Oslo Manual. Social Implications: in parallel to the operational results pointed out, the academic activity has enabled the improvement of economic enterprise that belong to settings and groups in social disadvantage